Academic satisfaction among university students during the COVID-19 pandemic: the influence of individual, social, and organizational variables - Testa, Silvia; Macagno, Alessia; Bertolino, Fabrizio; Cacciamani, Stefano; Grange, Teresa; Perrucci, Vittore; Piu, Angela; Timpano, Giuseppina; Cattelino, Elena (Frontiers in Education, 2023)
Academic satisfaction (AS) is considered by researchers and educators as a key variable to explain both academic success and the main problems of university students. AS is a complex construct affected by a range of factors, both internal and external to the individual. The aim of this study was to analyze the influence of certain individual (motivation and self-regulated learning), social (relationships with other students and with the instructor) and organizational (course organization and class attendance mode) variables on AS during the Covid-19 emergency, when face-to-face learning was replaced with online learning environments. We hypothesized a model in which AS would be directly influenced by the social and organizational variables, and indirectly influenced by the social, organizational, and individual variables via the mediation of perceived learning. The study sample comprised 104 students (83.7% female) with a mean age of 26.6 years (SD=9.8), enrolled on bachelor's or master's degree at a Northern Italian University. Participants filled out an online questionnaire, which they were instructed to complete with reference to a single course that they had taken during the second semester of the 2020-21 academic year. The hypothesized model, tested using a structural equation modelling technique for observed variables, offered an acceptable fit for the data [χ2(3) = 7.366, p = 0.061; RMSEA = 0.118; CFI = 0.976; SRMR= 0.010]. Perceived learning (R 2 =0.454), was influenced by self-regulated learning (β = 0.245, p<0.01) and course organization (β = 0.450, p<0.001); AS (R 2 =0.861) was influenced by relationship with the instructor (β = 0.634, p<0.001) and course organization (β = 0.209, p<0.01), as well as by the mediating variable, perceived learning (β = 0.230, p<0.001). The indirect effects of self-regulated learning and course organization on AS were statistically significant but of low magnitude. These outcomes point up the active role of students in terms of self-regulated learning and perceived learning and the key role of course organization and the student-instructor relationship in promoting students' AS during the Covid-19 pandemic, when the learning environment changed abruptly. These findings can usefully inform the work of instructors and instructional designers, including in non-emergency contexts.